Arabic Aphasia Research Through a Clinical and Linguistic Lens: A Systematic Review of Current Limitations and Future Directions - Tariq Khwaileh (8232351) (2025)
Background Aphasia has been widely investigated for English and other Indo‐European languages such as German, Dutch, Italian and Spanish. It has been reported that published studies on Arabic aphasia only comprised five studies, accounting for only 0.40% of the total literature on aphasia between 2000 and 2009. Aims The present paper is a systematic review of studies that have been published on Arabic aphasia. The main objective of this study is to review the body of aphasia literature on Arabic, to identify strengths and weaknesses in the available clinical resources for Arabic aphasia. Methods Preferred Reporting Items for Systematic Reviews and Meta‐Analyses (PRISMA) guidelines were followed. Five relevant databases were identified and searched using predefined keywords. A 6th source, Google Scholar, was also used to yield grey literature; these sources were screened on Scimago for quality assurance. Predefined eligibility criteria were then applied to the records that the initial search yielded. The final list of included studies was then qualitatively reviewed. Main Contribution The search yielded 48 studies. The resulting review identified a scarcity of research on assessment materials, efficacy of therapy and interventions and linguistic/psycholinguistic theory that underscores the development of clinical resources for Arabic aphasia. It suggested specific areas where development is required in each category. From the available research, it identified limitations in available materials for clinical assessment in Arabic aphasia. Specifically, that currently available materials are (a) primarily translations and adaptations of other languages rather than being developed with linguistically and culturally specific features of Arabic in mind; (b) are screening and short assessments rather than comprehensive batteries and (c) are not controlled for crucial psycholinguistic variables such as imageability and age of acquisition. Conclusions While research on Arabic aphasia has been growing in the past few years, it lacks in several areas of investigation, including certain methodological approaches, the varieties investigated, aphasia types and the formulation of valid assessment protocols and therapy interventions. Other Information Published in: International Journal of Language & Communication Disorders License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1111/1460-6984.70064